2002
DOI: 10.1038/sj.ijo.0802149
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E kinetics: influence of insulin resistance and type 2 diabetes

Abstract: BACKGROUNDS AND AIMS:Insulin resistance related to obesity and diabetes is characterized by an increase in plasma TG-rich lipoprotein concentrations. Apolipoprotein (apo) E plays a crucial role in the metabolism of these lipoproteins and particularly in the hepatic clearance of their remnants. The aim of this study was to explore apoE kinetics of obese subjects and to determine what parameters could influence its metabolism. METHODS: Using stable-isotope labelling technique ([ 2 H 3 ]-leucine-primed constant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Previous studies demonstrated that overproduction and slower catabolism of VLDL apoE explained the high concentration of VLDL apoE in hypertriglyceridemic subjects ( 25,27 ). Higher VLDL apoE concentration and PR were associated with elevated plasma and VLDL triglycerides ( 25,27 ). Our subjects exhibited overproduction of VLDL apoE, with concentrations of plasma and VLDL apoE within range of those previously reported in hypertriglyceridemic subjects ( 20,21,25,27 ).…”
Section: Data Interpretationsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous studies demonstrated that overproduction and slower catabolism of VLDL apoE explained the high concentration of VLDL apoE in hypertriglyceridemic subjects ( 25,27 ). Higher VLDL apoE concentration and PR were associated with elevated plasma and VLDL triglycerides ( 25,27 ). Our subjects exhibited overproduction of VLDL apoE, with concentrations of plasma and VLDL apoE within range of those previously reported in hypertriglyceridemic subjects ( 20,21,25,27 ).…”
Section: Data Interpretationsupporting
confidence: 63%
“…Higher VLDL apoE concentration and PR were associated with elevated plasma and VLDL triglycerides ( 25,27 ). Our subjects exhibited overproduction of VLDL apoE, with concentrations of plasma and VLDL apoE within range of those previously reported in hypertriglyceridemic subjects ( 20,21,25,27 ). It is, however, important to acknowledge that, in this study, VLDL apoE PR represents the transport of apoE through the VLDL pool.…”
Section: Data Interpretationmentioning
confidence: 47%
See 1 more Smart Citation
“…Kinetic studies of apoE (Bach-Ngohou et al, 2002) and apoAI (Frénais et al, 1997) have been previously described. Briefly, endogenous labeling of these apolipoproteins was performed by administration of L-[5,5,5-2 H 3 ]leucine (99.8 atom % 2 H 3 ; Cambridge Isotope Laboratories, Andover, MA) dissolved in a 0.9% saline solution and tested for sterility and the absence of pyrogens before the study.…”
Section: Subjects and Study Protocolmentioning
confidence: 99%
“…Most lipoprotein turnover studies with mass isotopes have used primed constant infusions (27,29,41,50,68,70,(99)(100)(101)(102)(103). Our results suggest that the reported FSRs and production rates are underestimates, with the percent error roughly equal to the plateau enrichment percent.…”
Section: Discussionmentioning
confidence: 52%